2024
DOI: 10.3390/dj12030082
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Temporomandibular Joint Disc Changes Associated with Effusion Using Magnetic Resonance Images

Camila Miorelli Girondi,
Sérgio Lúcio Pereira de Castro Lopes,
Celso Massahiro Ogawa
et al.

Abstract: The purpose of this study was to identify changes in the temporomandibular joint disc affected by effusion by using texture analysis of magnetic resonance images (MRIs). Methods: A total of 223 images of the TMJ, 42 with joint effusion and 181 without, were analyzed. Three consecutive slices were then exported to MaZda software, in which two oval ROIs (one in the anterior band and another in the intermediate zone of the joint disc) were determined in each slice and eleven texture parameters were calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, a recent study by Girondi et al reported the employment of MRI texture analysis (TA) in detecting changes in TMJ discs due to effusion. 34 The findings revealed that patients with effusion showed lower average imaging parameters, suggesting the presence of underlying changes that are not discernible through conventional visual inspection of MRI. 34 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For example, a recent study by Girondi et al reported the employment of MRI texture analysis (TA) in detecting changes in TMJ discs due to effusion. 34 The findings revealed that patients with effusion showed lower average imaging parameters, suggesting the presence of underlying changes that are not discernible through conventional visual inspection of MRI. 34 …”
Section: Discussionmentioning
confidence: 93%
“… 34 The findings revealed that patients with effusion showed lower average imaging parameters, suggesting the presence of underlying changes that are not discernible through conventional visual inspection of MRI. 34 …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations